EFFECT OF PARTIAL REPLACEMENT OF WHEAT AND RICE FLOUR BY MODIFIED STARCH ON CAKE AND BISCUIT QUALITATIVE AND SENSORY PROPERTIES - Mahdi, Zina HusseinAbdel; Shakir, Khalida Abdulrahman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate the effect of substituting different proportions (10%, 20%, 30%) of wheat flour and Amber rice with enzymatically modified starch  on qualitative and sensory characteristics of biscuits and cupcakes. The results showed a decrease in the thickness of wheat biscuits with an increase in the substitution percentage . The 30% substitution showed a significant difference compared to the others . Conversely, there was an increase in the diameter of biscuit samples, ranging from (42.00-48.30 cm), as well as the spread factor. The 30% substitution treatment showed a significant difference compared to the others. As for rice biscuits, the diameter and the spread factor values increased with increasing substitution rates. Sensory evaluation for rice and  wheat biscuits indicated that substitution rates of (0, 10 and 20)% achieved similarity in aroma , taste, symmetry of form, and crumb color. However, substitution rates of 30% for both products showed a darker color, more hardness, and the development of an acidic flavor . As for the cupcakes, the specific volume decreased with increasing substitution rates. The highest values for wheat cakes were recorded at substitution rates of 10% and 20%,being 3.19 and 3.00 cm3 /g respectively. The lowest values were recorded for WC3 and RC3 (2.60 ,1.61cm3 /g). The sensory evaluation for the cupcakes samples showed no significant differences as compared to the control sample in term of moisture, texture smoothness, crumb color, and crust color. Substitution at 10% and 20% showed similarity in terms of symmetry of form, crumb homogeneity, aroma ,taste and moisture. However, the 30% substitution rate resulted in a noticeable decline in product acceptance due to a decrease in volume , texture smoothness, reduced crumb homogeneity, as well as a darker color and an undesirable flavor